2017
DOI: 10.1021/acs.molpharmaceut.7b00434
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Presentation of Cationic Peptides on Supramolecular Nanofibers for Antimicrobial Activity

Abstract: Noncovalent and electrostatic interactions facilitate the formation of complex networks through molecular self-assembly in biomolecules such as proteins and glycosaminoglycans. Self-assembling peptide amphiphiles (PA) are a group of molecules that can form nanofibrous structures and may contain bioactive epitopes to interact specifically with target molecules. Here, we report the presentation of cationic peptide sequences on supramolecular nanofibers formed by self-assembling peptide amphiphiles for cooperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…[1][2][3][5][6][7][8] Increased activity has been reported by Beter et al upon comparing self-assembled C 12 -VVAGKKKGRW-NH 2 and KKKGRW-NH 2 nanobers with their corresponding soluble peptide molecules. 9 Similar results were reported by Chang et al for self-assembled cylindrical nanostructures made from C 16 -V 4 K 4 functionalised with an (AKKARK) 2 heparin binding Cardin-motif, which displayed strongly enhanced activity against Gram-negative bacteria above the critical micellar concentration (CMC). In the latter case it was suggested that self-assembly promotes the bacterial cytoplasmic leakage, causing blisters on disorganized membranes of Gram-negative bacteria.…”
Section: Introductionsupporting
confidence: 82%
“…[1][2][3][5][6][7][8] Increased activity has been reported by Beter et al upon comparing self-assembled C 12 -VVAGKKKGRW-NH 2 and KKKGRW-NH 2 nanobers with their corresponding soluble peptide molecules. 9 Similar results were reported by Chang et al for self-assembled cylindrical nanostructures made from C 16 -V 4 K 4 functionalised with an (AKKARK) 2 heparin binding Cardin-motif, which displayed strongly enhanced activity against Gram-negative bacteria above the critical micellar concentration (CMC). In the latter case it was suggested that self-assembly promotes the bacterial cytoplasmic leakage, causing blisters on disorganized membranes of Gram-negative bacteria.…”
Section: Introductionsupporting
confidence: 82%
“…The amyloids can then disrupt the cell membrane. Similar interaction between self-assembled fibers and lipid vesicles or bacterial membranes has been discovered with surfactant-like peptides 14,15 and peptide amphiphiles 16 . Different from AMPs, the membrane disrupting mechanisms of amyloids have been commonly related to peptide assembly.…”
Section: Introductionsupporting
confidence: 59%
“…Overall, our data indicate that peptide aggregation should be taken into account as an additional method to vary the effective hydrophobicity of membrane-active HDPs, and therefore their cell-selectivity. Peptide aggregation or ordered self-assembly presents additional advantages, since it reduces susceptibility to proteolytic degradation, it affects the pharmacokinetics and pharmacodynamics [72,[79][80][81], and it allows the local release of a high peptide concentration at a single site in the membrane [82][83][84]. Finally, aggregates of membrane-active peptides could be even considered for the entrapment of small-molecule drugs inside the hydrophobic core of the particles, for targeted delivery [85][86], leading to the development of new therapeutic tools based on synergistic effects [87].…”
Section: Discussionmentioning
confidence: 99%